2021
DOI: 10.1007/s40843-021-1907-3
|View full text |Cite
|
Sign up to set email alerts
|

Creation of Mo active sites on indium oxide microrods for photocatalytic amino acid production

Abstract: As an n-type semiconductor, In 2 O 3 is considered a promising photocatalyst for producing amino acids using biomass derivatives as precursors. However, similar to other intrinsic semiconductors, In 2 O 3 suffers from poor charge dynamics. Herein, we show the synthesis of Mo-doped In 2 O 3 (Mo-In 2 O 3 ) with a porous rod-shaped structure through a onestep solvothermal reaction followed by calcination. Under visible-light irradiation, Mo-In 2 O 3 achieves a high conversion rate of 81% for the reaction that tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…When compared to the representative photocatalytic systems, [9,10] Ru 1 /CdS predominates in terms of conversion, selectivity, yield, and alanine formation rates (Figure 3d). The activity of the Mo‐In 2 O 3 catalyst [11] was close to that of Ru 1 /CdS, but the system used toxic N,N‐dimethylformamide (DMF) as a solvent and the reaction was carried out at low reactant concentrations (the ratio of lactic acid to catalyst is 18 : 1, which is about 1/8 of this work). Although the thermocatalytic system showed higher conversion of lactic acid and yield of alanine formation, [6b] the reaction rate (2.4 mmol Ala ⋅ g cat −1 ⋅ h −1 ) was only about 1/20 of that of Ru 1 /CdS and it requires high temperature (220 °C) and pressure of H 2 (1 MPa), thus highlighting the superiority of our system (Table S1).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…When compared to the representative photocatalytic systems, [9,10] Ru 1 /CdS predominates in terms of conversion, selectivity, yield, and alanine formation rates (Figure 3d). The activity of the Mo‐In 2 O 3 catalyst [11] was close to that of Ru 1 /CdS, but the system used toxic N,N‐dimethylformamide (DMF) as a solvent and the reaction was carried out at low reactant concentrations (the ratio of lactic acid to catalyst is 18 : 1, which is about 1/8 of this work). Although the thermocatalytic system showed higher conversion of lactic acid and yield of alanine formation, [6b] the reaction rate (2.4 mmol Ala ⋅ g cat −1 ⋅ h −1 ) was only about 1/20 of that of Ru 1 /CdS and it requires high temperature (220 °C) and pressure of H 2 (1 MPa), thus highlighting the superiority of our system (Table S1).…”
Section: Resultsmentioning
confidence: 98%
“…[10] Jiang et al recently synthesized Mo-doped In 2 O 3 micro rods using an indium-containing metal-organic framework (MIL-68) as the structural directing template, which showed a higher rate of alanine formation up to 36.8 mmol Ala • g cat À 1 • h À 1 , while the reaction mechanism remains unexplored. [11] Since the pioneering work of Zhang et al in 2011, [12] single-atom catalysts (SAC) have emerged as a powerful class of catalysts with unique properties (e.g., uniform active sites, theoretical 100 % atomic utilization) compared to the traditional homo-and heterogeneous catalysts, and present exciting activity and selectivity in many catalytic reactions including hydrogenation, [13] Suzuki coupling, [14] photo-(electron)catalytic hydrogen evolution, [15] CO 2 reduction, [16] nitrogen fixation, [17] and transfer hydrogenation. [18] Recently, Li's group reported that atomically dispersed Pt on CdS selectively produced α-keto acids from α-hydroxy acids via oxidation reactions, while Pt nanoparticles on CdS switch the product selectively to CÀ C coupling reactions to produce tartaric acid derivatives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…the conversion of LA to alanine with a conversion rate and reaction rate of 0.407 mmol h −1 and 0.369 mmol h −1 , respectively. 92 Doping of Mo enhances bulk and interfacial charge transfer, whilst forming Mo-O-In bonds as new active sites due to replacing In 3+ of the In 2 O 3 lattice with Mo 5+ . 92 In short, the activity of the reaction can be improved by altering the local electronic environment, enhancing the efficiency of photocarrier migration, and establishing new reactive sites.…”
Section: Amino Acidsmentioning
confidence: 99%
“…Zheng et al reported the use of Mo-doped indium trioxide (Mo-In 2 O 3 ) as a photocatalyst for the conversion of LA to alanine with a conversion rate and reaction rate of 0.407 mmol h −1 and 0.369 mmol h −1 , respectively. 92 Doping of Mo enhances bulk and interfacial charge transfer, whilst forming Mo–O–In bonds as new active sites due to replacing In 3+ of the In 2 O 3 lattice with Mo 5+ . 92 In short, the activity of the reaction can be improved by altering the local electronic environment, enhancing the efficiency of photocarrier migration, and establishing new reactive sites.…”
Section: Photocatalytic Oxidation For C–c/c–o Bond Cleavagementioning
confidence: 99%